Influence of dopant size and doping method on the structure and thermoelectric properties of PBTTT films doped with F6TCNNQ and F4TCNQ. Issue 46 (29th October 2020) - Vijayakumar, Vishnu; Durand, Pablo; Zeng, Huiyan; Untilova, Viktoriia; Herrmann, Laurent; Algayer, Patrick; Leclerc, Nicolas; Brinkmann, Martin
Abstract : Better ordering of dopants in PBTTT is achieved by progressive intercalation, leading to improved thermoelectric power factors in oriented films. Abstract : Doped polymer semiconductors are ideal candidates to capture waste heat under ambient conditions using modest temperature gradients close to room temperature. Mastering the doping mechanism of polymer semiconductors is therefore crucial to enhance the performance of these materials. This study focuses on the structure–property correlations in oriented films of poly(2, 5-bis(3-dodecyl-2-thienyl)thieno[3, 2- b ]thiophene) (C12 -PBTTT) doped with 1, 3, 4, 5, 7, 8-hexafluoro-tetracyanonaphthoquinodimethane (F6 TCNNQ) and 2, 3, 5, 6-tetrafluoro-7, 7, 8, 8-tetracyano-quinodimethane (F4 TCNQ). Slower diffusion of the larger F6 TCNNQ molecules in PBTTT crystals results in a better ordering upon intercalation in the layers of alkyl side chains as compared to F4 TCNQ. Both the higher degree of polymer chain oxidation and ordering of F6 TCNNQ-dopants in the C12 -PBTTT crystals account for the improved electrical conductivity and thermoelectric properties. A new doping protocol called "incremental concentration doping" leads to electrical conductivities of up to 2400 S cm −1 and thermoelectric power factors of 530 ± 200 μW m −1 K −2 in aligned C12 -PBTTT doped with F6 TCNNQ. The progressive intercalation of dopants helps preserve the high level of order initially present in the aligned C12 -PBTTT films, hence, reaching higher charge mobilities. The correlations between thermopower S and charge conductivity σ measured parallel and perpendicular to the polythiophene chain follow two master curves regardless of the chemical nature of the dopant: S ∝ σ −1/4 along the chain direction whereas S ∝ −ln( σ ) perpendicular to the chains.